Contemporary surgical management of fracatures & complications - Ilyas, Asif (Jaypee-Highligts Medical Publishers, 2013)
his two volume set is a complete guide to the surgical management of fractures and complications. Volume one discusses the upper extremity and spine and Volume two examines the pelvis and lower extremity. Each chapter discusses a different type of fracture, providing a step by step guide through history, clinical presentation, diagnostic testing, imaging, treatment and complications.